Cecal dilatation and distension in a Holstein calf - Alves, Bárbara de Andrade; Mendonça, Carla Lopes de; Afonso, José Augusto Bastos; Gonçalves, Eldo; Colares, Raquel Ribeiro; Lima, Thatyane Carla de; Arenales, Alexandre (Brazilian Journal of Veterinary Pathology, 2021)
Cecal dilatation and distention is an important disorder in early lactation dairy cows, however, reports describing theanatomical pathology findings of this condition are scarce in the literature. Etiopathogenesis of cecal dilatation and distention isoften attributed to high concentrate feeds, but there is also evidence of myoelectrical dysfunction contributing to its occurrence.Diagnosis is often made based on physical exam findings, with the contribution of ancillary exams. This paper aims to describe acase of cecal dilatation with clinical, laboratorial and pathology findings of a 5-month-old Holstein calf that presented abdominaldistension, positive succussion of the right flank and mild dehydration. Clinical pathology findings included neutrophilicleukocytosis with regenerative left shift and elevated ruminal chloride. Ultrasonographic examination of the right abdomenshowed distended and hypomotile intestinal loops. Despite that, due to the patient’s age, which prevented rectal palpation, andlack of some characteristic clinical and clinical pathology findings, diagnosis was only possible post mortem. Macroscopical andmicroscopical findings demonstrated cecum dilatation with edema, hemorrhage and thrombi. Despite being well known by largeanimal clinics, anatomical pathologists must be aware of this condition.